INFLUENCE OF ELECTRONIC WORD OF MOUTH (EWOM) ON CONSUMER PURCHASE DECISIONS: A STUDY WITH REFERENCE TO KOTTAYAM DISTRICT, KERALA - Kuriakose, Jinnu Anna (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study explores the influence of Electronic Word of Mouth (eWOM) on consumer purchasing decisions in the Kottayam district. In the age of digital transformation, when customers rely of the internet and social media, eWOM has become a significant factor in shaping consumer attitudes and behaviours. This research utilized a survey method, collecting primary data from 100 respondents through a structured questionnaire. The study found that most consumers (90%) are aware of eWOM and actively search for information online before making a purchase. Shopping websites were identified as the most influential eWOM platform, with reviews being the most preferred form of eWOM. The credibility and trustworthiness of the information source were ranked as the most critical factor influencing purchase decisions. Overall, the study concludes that eWOM has a significant and positive influence on the purchasing behaviour of consumers, who rely on it to compare brands, make informed decisions, and build trust.